Enrichment with Growth - Klein, Michael (2012)
This essay first sets out the "business model" problems entailed by corruption and their effects as well as implications for economic growth. Key issues are the need for secrecy and co-operation with partners in crime. Dealing with these leads to behavior which is ostensibly bizarre and undermines economic efficiency, but is in fact a rational way of managing corrupt practices. However, different economic policies can be pursued that are compatible with corruption. Some are more pro-growth than others. Pro-growth corrupt policies hold the promise of enriching the corrupt elite more in absolute terms even though the share of national wealth diverted may be smaller. The most effective pro-growth polices that help enrich an elite resemble fairly orthodox economic policy prescriptions. Eventually the abolition of corruption holds the greatest promise to enhance growth and with it the wealth of elites. The expectation of such growth may explain why more and more political elites pursue "sound" economic policy and may embrace anti-corruption efforts, while securing legal ways of enrichment for themselves. Country examples illustrate policy approaches with different combinations of enrichment and growth properties.